Characterization of urban aerosol sources in Debrecen, Hungary - Kertész, Zsófia; Szoboszlai, Zoltán; Dobos, Erik; Borbély-Kiss, Ildikó (Acta Geographica Debrecina Landscape & Environment series, 2008)
Debrecen is an average middle European city from the point of view of aerosol pollution. Its location makes the city an ideal place for observing aerosol transport processes. Systematic investigation of atmospheric aerosol of the east-Hungarian region has been performed in the Institute of Nuclear Research of the Hungarian Academy of Sciences for 20 years by accelerator based elemental analytical technique. As a complementation of this research we observed the size distribution and short-term time variation of the elemental component of fine (PM2.5) and coarse (PM10-PM2.5) urban aerosol in the frame of sampling campaigns during 2007 and 2008 in a downtown site of Debrecen. Meteorological parameters were also recorded parallel to the aerosol sampling. Elemental concentrations (Z ≥ 12) were determined by particle induced X-ray emission (PIXE) analytical technique at the Laboratory of Ion Beam Applications (IBA) of the ATOMKI. On the obtained database six sources of the urban aerosol were identified: 2 types of soil, domestic heating, sulphate originating from long range transport processes, an unidentified source enriched with chlorine and traffic. Emission episodes were also observed. The short-time variation of urban aerosol combined with meteorological data and with mass size distribution serves as a basis to reach a better understanding of the aerosol sources in receptor areas, to select local emission and long range transport episodes, to follow the evolution of aerosol, and to make a better estimate on the health impact.